Pengaruh Penambahan Abu Sekam Padi Terhadap Peningkatan Kualitas Minyak Mandar: The Effect of Rice Husk Ash Addition on The Increasing of Mandar Coconut Oil Quality - Musafira; Dzulkifli; Hikmah; Nizar (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Mandar coconut oil is one of the coconut processed products, which has become superior product in West Sulawesi especially in Majene regency. Unfortunately, the Mandar coconut oil can’t be used more than a month because the water content and free fatty acid content of the oil have exceeded the maximum standard of SNI, so it can adversely affect on health. On the other hand, the existence of rice husk in Indonesia itself especially in West Sulawesi has not received attention and is limited to a few needs such as for ash or livestock feed, and the rest is thrown away. This research aims to determine the effect of rice husk ash addition on the increasing of Mandar coconut oil quality. Completely randomized design was used in this research with 6 rice husk ash concentration variation levels i.e. 0%, 5%, 10%, 15%, 20% and 25%. The result shows that the addition of rice husk ash with 10% to 25% can reduce the water content of the oil until the quality standard of SNI is full filled. The highest reduction of water content was reached with 25% of rice husk ash concentration with 81% of reduction percentage. While, the addition of rice husk ash with 15% concentration can reduce the free fatty acid content of Mandar coconut oil until 32%.